Narcolepsy: an interface among neurology, immunology, sleep, and genetics - Fernando Morgadinho Santos Coelho (Arquivos de Neuro-Psiquiatria)
Narcolepsy is a primary disorder of the central nervous system resulting from genetic, environmental, and immunological interactions defined as excessive daytime sleepiness plus cataplexy, hallucinations, sleep paralysis, and sleep fragmentation. The pathophysiology is not entirely known, but the interaction among genetic predisposition, environmental exposition, and immune component with consequent hypocretin-1 deficiency is the model to explain narcolepsy type I. The mechanism of narcolepsy type II is less understood. There is a delay of over ten years for the diagnosis of narcolepsy around the world. Patients with narcolepsy have many comorbidities with a negative impact on quality of life. The treatment of narcolepsy must contain an educational approach for the family, coworkers, and patients. Scheduled naps and sleep hygiene are essential to minimize the dose of medications. Much progress has been seen in the pharmacological treatment of narcolepsy with new stimulants, different presentations of oxybate, and recent studies with orexin agonists. Narcolepsy is a rare disease that needs to be more understood and highlighted to avoid delayed diagnosis and severe disabilities in patients.